Values and Ethics in Social Work - Beckett, Chris; Beckett, Chris; Maynard, Andrew; Jordan, Peter (SAGE Publications, 2017)
An awareness of one$1 (Bs own ethical assumptions and how these inform everyday practice is crucial for all student social workers. Social workers who genuinely wish to do the right thing by their services users have no alternative but to constantly think and rethink the principles and assumptions that inform their actions, and this book supports them on their journey to do just that. This third edition is set out in two parts: Part I deals with broad ideas about values and ethics in general, looking at philosophy, religion and politics, as well as the duty of realism. Part II takes the discussion further, looking at how these general principles are relevant to everyday practice, with chapters on the use and misuse of power, the idea of self-determination, and the challenges of working with people whose experience and outlook are different to one$1 (Bs own.s